SOCIETY MANAGEMENT AS A TOPOLOGICAL DIVERSITY - Kharchenko, Yulia (Proceedings of the National Aviation University Series Philosophy Cultural, 2022)
It is shown that society as an ontological diversity fixes in its space an extremely wide range of parametric possibilities. Society is constructed through the use of parametric modeling using the parameters of the elements of the ideal model and the relationships between these parameters. The aim of the study is to conceptualize society as topological diversity and changeable complexity in terms of philosophical ontology, social philosophy and topology. The key task of this study is to analyze the mechanisms of management of society as a topological diversity. Topology as a methodological principle is used when comparing ontological diversity with topological diversity, as well as in describing society as a complexity in which ontological spaces intersect. The conclusions substantiate the argument that the control mechanism is created and purposefully changed, modernized, depending on the functional and technological capabilities and innovative models existing in each separate system.